2019
DOI: 10.1177/1120700019831665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pelvic tilt and rotation on cup orientation in standing anteroposterior radiographs

Abstract: Background: Individual pelvic tilt and rotation have wide variability that can affect the measurement of cup orientation in anteroposterior (AP) radiographs. The purpose of this study was to analyse the effect of pelvic tilt and rotation on radiographic measurements of cup orientation. Methods: A total of 53 patients (63 hips) were included in this study. The patients underwent a computed tomography study with standing AP pelvis radiographs taken both preoperatively and approximately 3 months postoperatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, the X-ray offset was also neglected by the Ackland algorithm used in their method. In another clinical study, Yun et al used 2D-3D matching software to compare the difference in the RA angles between the supine and standing positions and found that there was a negative correlation of the pelvic longitudinal rotation with the RA angle of the right cup but a positive correlation with the left cup in both supine and standing positions (135,136).…”
Section: D-3d Registration Methodsmentioning
confidence: 99%
“…Nevertheless, the X-ray offset was also neglected by the Ackland algorithm used in their method. In another clinical study, Yun et al used 2D-3D matching software to compare the difference in the RA angles between the supine and standing positions and found that there was a negative correlation of the pelvic longitudinal rotation with the RA angle of the right cup but a positive correlation with the left cup in both supine and standing positions (135,136).…”
Section: D-3d Registration Methodsmentioning
confidence: 99%
“…With the widespread use of CT, the ACEA CT has begun to be used to determine the anterior coverage of the hip instead of the ACEA FP. The reproducibility of the ACEA CT is better, but its correlation with the ACEA FP in patients with hip dysplasia is not yet clear [ 10 ]. To address these problems, we carried out this study.…”
Section: Discussionmentioning
confidence: 99%
“…The ACEA CT is measured on the CT sagittal plane, which is obtained in the supine position, while the ACEA FP is measured on FP radiographs, which are obtained in the standing position. These variations lead to differences in the measurement results [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because standing radiography can recreate the state of the hip during body weight loading, the pelvic tilt was not normalized. [35] On the FP radiographs, the ACEA was measured by the angle between the line joining the midpoint of the femoral head to the anterior rim of the acetabular sourcil and its vertical line. The normal reference value for the ACEA is 20-40°.…”
Section: Methodsmentioning
confidence: 99%